Bridging the Global Divide: Building Local Capacity for Open and Reproducible Science - Fyneboy nwachukwu Macdickson Celt (Enago Article for Open Access, 2025)
Open science has redefined global research by promoting transparency, collaboration, and accessibility. Yet, despite significant progress, a gap persists between those who can fully participate in open and reproducible science and those who cannot. This article, written for Open Access Week 2025, explores how to bridge that divide by focusing on three interconnected goals: closing reproducibility gaps, building local capacity, and rethinking global participation. It argues that openness must move beyond access to information and include access to opportunity, skills, and decision-making. Drawing on global initiatives such as The Turing Way and UNESCO’s Recommendation on Open Science, the paper emphasizes that reproducibility is achievable only when local capacity is strengthened and inclusivity is prioritized. Ultimately, it calls for a shift from viewing openness as a policy to embracing it as a daily practice, one rooted in empathy, equity, and collaboration to create a truly global and participatory research ecosystem